A Rare Case of Life-Threatening Extensive Mucocutaneous Adverse Reaction Induced by Docetaxel in a Breast Cancer Patient: Toxic Epidermal Necrolysis, a Case Report with Review of Literature - Shrivastava, Shiv Prasad; Elhence, Aditya; Jinwala, Prutha; Bansal, Shashank; Chitalkar, Prakash; Bhatnagar, Shweta; Patidar, Rajesh; Asati, Vikas (Indian Journal of Medical and Paediatric Oncology, 2022)
Fever and extensive necrosis with 30% or more epidermal involvement along with mucous membrane is known as toxic epidermal necrolysis (TEN). It is a life-threatening mucocutaneous disease and is usually drug induced. We report a rare case of docetaxel-induced TEN. A patient with metastatic breast carcinoma received single agent docetaxel and developed severe skin and mucous membrane reaction involving more than 30% of the skin, and managed conservatively in intensive care unit but she succumbed to her illness. Although common toxicities reported with docetaxel include alopecia, nail damage, myelosuppression, and erythema multiforme major, TEN after docetaxel is very rare and can be a life-threatening complication as in our case.
Keywords: docetaxel; toxic epidermal necrolysis; breast cancer; case report